წყნარი ოკეანის ომის მიზეზების კონცეფცია და შეფასება აშშ საზოგადოებრივ-პოლიტიკურ წრეებში - ხუბაშვილი, ლეილა (ია); ოქრიაშვილი, გიორგი (უნივერსიტეტის გამომცემლობა, 2021)
The scientifi c study of this issue actively began after the victory of the United States over Japan. Numerous publications have been published both in Japan and in the United States, on controversial events of 1941-1945. Memoirs of war participants have been published, which took the historiographical research of the war to the new level. At the end of the war, two major scientifi c schools were established in the United States: the “offi cial” and the “revisionist.” The fi rst scientifi c concept of “revisionists” was formed in Charles Austin Beard’s works: American Foreign Policy in the making 1932-1940, N-Y 1946, “President Roosevelt and the Coming of the War 1941”, N-Y 1948. The revisionists argued that the main responsibility lay with the President and the State Department, whose policies had put economic pressure on Japan, which had begun a war in response. In the late 1980s and early 1990s, several important works appeared in American historiography that supported the offi cial version of the attack on Pearl Harbor, but did little to analyze the cause-and-eff ect, e.g. Steve Horn’s “The Second Attack on the Pearl Harbor” (Annapolis. 2005). The problem, elaborated by this school, was the pre-war foreign policy of the United States. The issue of the attack on Pearl Harbor plays an important role here; the “revisionists” argued that U.S. policy before the war was built to provoke a military confl ict with Japan. In recent years, the theme of Pearl Harbor has become relevant again, with new developments in books by Emily S. Rosenberg (Emily S. Rosenberg, “A Date Which Will Live: Pearl Harbor in American Memory”, Durham, 2003) and Kent D. Richardson (Kent D. Richardson, “Refl ections of Pearl Harbor: An Oral History of December 7, 1941”, Greenwood, 2005). As for Japanese historiography, for example, we will name two monographs translated from Japanese into Russian: “History of the Pacifi c Ocean”, in fi ve volumes, Ed. Osami Seijiro, Moscow 1958 and Takushiro Hattori, “Japan in the War of 1941-1945”, Saint Petersburg, 2000. In them, Pearl Harbor is seen as a coercive move caused by humiliating and brutal policy, conducted by the United States. Works of Fujiwara Akira and Hata Ikuhiko are written in the same spirit, as well. Finally, the following should be noted as a conclusion: 1. Japan has regarded the US military-political leadership as a major rival in the Pacifi c since the 1920s, specifi cally after the Washington Treaty; 2. Since 1931, the United States, which considered war in the Pacifi c Ocean inevitable, sought to exert economic pressure on Japan and redirect its aggression towards the Soviet Union or China. An example of this is the Tanaka Memorandum. 3. After 1936, the United States was preparing for war. This is evident not only by the development of a war scenario, but also by the budget, the expansion of the fl eet and aviation along with the bases, the creation of submarines and landing forces; 4. As soon as the attack on Pearl Harbor took place, the offi cial concept of the causes of war began to develop at the highest level, led by President Roosevelt, and the press actively distributed its version to the public; 5. On the anniversary of the attack on Pearl Harbor, two major events took place: the results of the Knox Commission were published, and a decision was made to set up a special commission and hold Kimmel and Short in charge. The results of the Roberts Commission have been published. On August 29, 1945, President Truman presented a report of the Military and Naval Commission at a press conference, which led to the establishment of a commission of inquiry by Congress, which investigated the December 7 disaster. Pearl Harbor has become a symbol of the tragic beginning of the war.
The concept and assessment of the causes of the Pacifi c War in the US socio-political circles
Keywords: აშშ; წყნარი ოკეანის ომი; მეორე მსოფლიო ომი; USA; Pacific War; World War II